Versatile Superlattice-enhanced Quantum Sensing - Toa, Zi S.D.; Paterova, Anna V.; Chekhova, Maria V.; Krivitsky, Leonid A. (Optics InfoBase Conference Papers, 2022)
Versatile and sensitive quantum sensors are important in various applications. A crystal superlattice is capable of sensitively measure low and high infrared analyte concentration by respectively measuring fringe maximum intensity and visibility in the visible.
CRIS-Team Scopus Importer:2023-03-27